Peran dan Kontribusi Pendidikan Agama Islam dalam Pemberdayaan Perempuan di Lingkungan Masyarakat - Ni’mah, Nita Jannatun; Anggani, Rika Febri; Fitria, Siti Nizarotul; Najichah, Amalia Fajriyyatin (Unit Pelaksana Teknis Penelitian dan Pengabdian pada Masyarakat (UPT-P4M) STAI Auliaurrasyidin Tembilahan, 2024)
Through current approaches in the social, economic and political spheres, recent research suggests Islamic religious education can provide a strong foundation for women in developing their potential and achieving gender equality. This research aims to explore the important role of Islamic religious education in empowering women socially, economically and politically and to provide a deeper understanding of its contribution to enhancing women's participation in public life. This research is a qualitative type of literature study by making library materials as the main data source, using the main reference to the phenomenon of the prophetic era and then correlating it with the related verses and stories listed in the Qur'an. The results showed that Islamic Religious Education has an important role in improving the quality of individuals. In addition, Islamic religious education does not provide rejection of the role of women in any aspect. Therefore, the Qur'an also explicitly says about equality between men and women.